FACTORS THAT INFLUENCE THE INTEREST OF GEN-Z MUSLIM CONSUMERS IN PURCHASING FOOD ON THE ONLINE FOOD SERVICE DELIVERY SYSTEM APPLICATION - Marliyah, Marliyah; Yanti, Nursantri; Rafli, Mhd (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the factors that influence Gen-Z Muslim consumer interest in making food purchases on the online food service delivery system application which is divided into three variables, namely product quality, price, and halal awareness. This study uses quantitative methods, and data collection techniques by distributing questionnaires and sample number in this study was 100 students at the State Islamic University of North Sumatra using purposive sampling techniques. The data were analyzed using multiple linear regression methods. The results of the study indicate that product quality and price have a significant effect on purchase intention, and halal awareness has no significant effect on purchase intention, and the results of the simultaneous test hypothesis show that product quality, price, and halal awareness simultaneously affect purchase intention. Keywords : Product Quality ; Price ; Halal Awaraness ; Purchase Intention